All hail, the baklang kanal! subversive frivolity in two Filipino influencers - Cabbuag, Samuel (Plaridel, 2022)
Access online through this link: https://www.plarideljournal.org/article/all-hail-the-baklang-kanal-subversive-frivolity-in-two-filipino-influencers